Analysis of Waste Management at TPS Sardo in the Community of RT 01 Gajayana Merjosari Village, Lowokwaru District, Malang City - Amalia, Firda Nur (Maliki Interdisciplinary Journal, 2025)
Waste is an inseparable part of daily activities and becomes an environmental problem that needs to be managed properly so as not to cause negative impacts on society. This study aims to identify waste management problems in the Sardo Temporary Shelter (TPS) used by the community of RT 01 Gajayana, Merjosari Village, Lowokwaru District, Malang City, and design appropriate solutions to overcome these problems. The research method used was qualitative with a descriptive observational approach, including field surveys, focus group discussions, open interviews, and literature studies. The research participants consisted of the head of the RT and several residents of RT 01 Gajayana as community representatives. The results of the analysis showed that waste management at TPS Sardo has not been running optimally, characterized by inadequate facilities, as well as the low discipline of residents in disposing of waste according to schedule. Based on these findings, the researchers designed a waste management project that includes improving facilities, making innovative products such as paving blocks from recycled waste, and increasing public awareness. The last step taken is socialization to residents to increase active participation in good and correct waste management. It is recommended that the implementation of mutual cooperation on a regular basis and the allocation of a budget for land acquisition as a place for planting waste.